Differentiation of Parkinson's disease tremor and essential tremor based on a novel hand posture. (2022) - Mahendran, Sujitha; Bichsel, Oliver; Gassert, Roger; Baumann, Christian R.; Imbach, Lukas L.; Waldvogel, Daniel
Abstract: Background: Tremor is one of the most common movement disorders but the correct diagnosis of tremor disorders, especially the differentiation between Parkinson's disease tremor (PT) and essential tremor (ET) remains a challenge for clinicians. Method: We examined a novel hand position to distinguish PT from ET. We prospectively collected accelerometric tremor data in 14 ET patients and 14 PT patients with arms and hands fully stretched against arms stretched and hands relaxed, i. e. hanging down. The total acceleration from the three pairwise-perpendicular accelerometric axes during the 1-minute blocks of the two hand positions were computed and high-passed filtered at 2 Hz. The power spectral density during each hand position was calculated and summed up over the frequency domain. Results: Our results showed a significantly higher occurrence of tremor in the hands hanging down position in PT patients compared to ET patients ( p = 0.0262). Moreover, in PT patients the tremor intensity significantly increased when transitioning from the stretched hand position to the hanging-down position (83 % of cohort) and vice versa in ET patients (75 % of cohort). Conclusion: In conclusion, the new hand posture can differentiate between PT and ET with high accuracy (sensitivity 83 %, specificity 75 % for PT) and may be a helpful tool in the clinical assessment of tremor.